The letters of the university of Oxford on withdrawal of obedience from pope Boniface IX - Harvey, Margaret M. (Studies in church history, 1975)
In this paper I shall discuss two letters apparently sent in 1399 by the University of Oxford to Richard II, in answer to the king’s request for advice on whether to withdraw obedience from pope Boniface IX in an endeavour to end the great schism. There has been a controversy about which letter represents the official view of the university, and this argument has largely arisen, I suspect, because hitherto one of the letters has been studied in its printed form which is incomplete and does not give a true idea of its arguments. I will also consider how these letters are to be seen in the context of the final stages of Richard II’s policy on the schism.